Cadmium-induced toxicity in Meretrix meretrix ovary is characterized by oxidative damage with changes in cell morphology and apoptosis-related factors - Bai, Binbin; Yang, Yuqing; Wei, Jinyan; Zheng, Qi; Wang, Mengci; Chang, Alan Kueichieh; Ying, Xueping (Frontiers in Marine Science, 2022)
Cadmium (Cd) is one of the most common pollutants in the environment. It can cause irreversible tissue damage and apoptosis in invertebrates. This study investigated the relationship between Cd exposure and oxidative damage and apoptosis in the ovarian cell of the clam Meretrix meretrix. The clams were exposed to different concentrations of Cd2+ (0, 1.5, 3, 6 and 12 mg L−1) for 5 days, and the accumulated level of Cd2+ in the ovarian tissue, and the degree of oxidative damage, changes in morphology and the response of apoptosis-related factors in the ovarian cell were determined. The bioaccumulation of Cd2+ and the levels of reactive oxygen species (ROS), malondialdehyde (MDA), protein carbonylation (PCO), and DNA-protein crosslinking (DPC) in the ovary were found to increase significantly when the clams were exposed to increasing concentrations of Cd2+. The structure of the ovarian tissue was severely damaged, and the ovarian cells displayed an irregular arrangement. The results of AO/EB staining and flow cytometry showed that the apoptotic rate of the ovarian cells increased with increasing Cd2+ concentrations. The activities of caspase-3, -8, -9, and the mRNA levels of p53, Bax and Caspase-3 in the ovary were also significantly increased. Furthermore, the level of p53 mRNA was positively correlated with the levels of MDA, PCO, DPC and ROS, but negatively correlated with the levels of total antioxidant capacity (T-AOC) and Bcl-2 mRNA. Taken together, these results indicated that Cd2+ exposure would result in oxidative damage and apoptosis for the ovarian cells, suggesting that Cd2+ toxicity could negatively affect the reproductive capacity of M. meretrix, thus threatening the reproductive development of the shellfish.